A tunnel grouting material and preparation method thereof

By using mixed materials such as semi-carbonized steel slag powder, phosphorus slag powder, calcium carbide slag and desulfurization ash, combined with water reducing agent and SAP particles, the expansion and impermeability problems of cement-based grouting materials are solved, and an efficient tunnel structure is achieved Sealing and long-term anti-seepage effects reduce production costs.

CN119143452BActive Publication Date: 2025-01-14SHIJIAZHUANG TIEDAO UNIV +1

Patent Information

Application Number
CN202411614084.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-14
Estimated Expiration
2044-11-13
Patent Text Reader

Abstract

The invention relates to the technical field of cement-based building materials, and in particular to a tunnel grouting material and a preparation method thereof. The invention adopts cement as a cementitious material and adds a large amount of industrial solid waste as an admixture, wherein semi-carbonized steel slag powder is prepared by modifying steel slag, and phosphorus slag powder, carbide slag and desulfurization ash are combined as admixtures, and a water reducer and SAP particles are added as admixtures. The raw materials cooperate with each other to prepare a grouting material with good fluidity, compactness and mechanical properties, and at the same time, has a long-term expansion effect in a humid environment and good sealing and anti-seepage effects, and at the same time realizes efficient utilization of industrial solid waste.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cement-based building materials, in particular to a tunnel grouting material and a preparation method thereof. Background Art

[0002] Transportation engineering construction faces many tunnel construction technologies. The tunnel construction process includes many steps, among which grouting technology is widely used. It has the functions of dense filling, maintenance structure reinforcement, leak prevention and anti-seepage, etc. It can strengthen the tunnel surrounding rock, ensure the stability of the tunnel structure and reduce soil erosion.

[0003] Commonly used grouting materials are divided into inorganic grouting materials and organic grouting materials. Inorganic grouting materials are divided into cement-based, geopolymer, water glass and other types, which have the advantages of good fluidity and low price. Organic grouting materials are divided into pure polymer and composite polymer types, which have higher toughness and good filling density, but higher price and easy to cause environmental pollution. Cement-based grouting materials are still the most widely used grouting materials.

[0004] Prior art CN101255698A discloses a double-liquid high-pressure grouting liquid, which uses ordinary Portland cement and water glass as slurry materials. CN109437771A discloses a grouting material, which includes Portland cement, gypsum, fly ash, an accelerator, and an expansion agent. CN102351480A discloses a high-performance grouting material, which is prepared from a matrix component and an external component. The matrix component consists of ordinary Portland cement, fly ash, mineral powder, an expansion agent and water, and the external component consists of a naphthalene-based high-efficiency water reducer, sodium gluconate, sodium tripolyphosphate, and an air entraining agent.

[0005] However, in order to achieve the sealing effect, the cement-based grouting in the above-mentioned prior art must ensure a certain expansion effect. Most of them use fast-hardening cement such as sulphoaluminate cement, which has a fast setting time. However, its later strength is prone to shrinkage. Some prior arts add expansion agents, which are expensive and easily cause the loss of fluidity of the grouting material. Moreover, whether it is using expansive fast-hardening cement or adding expansion agents, its expansion period is mostly within 90 days. The tunnel structure often has complex hydrological conditions, and micro-cracks and pressurized water seepage often exist. The grouting material needs to have the performance of timely blocking and long-term anti-seepage. In addition, the prior art mostly uses fly ash, mineral powder, etc. as admixtures. With the soaring prices of such admixtures, the production cost of the grouting material is greatly increased.

[0006] With the requirements for ecological and environmental protection, the reuse of bulk industrial solid waste has become a research hotspot in the building materials industry. Among them, the utilization rate of industrial solid wastes such as steel slag and phosphorus slag is relatively low. Steel slag comes from the iron smelting industry. Its chemical composition is similar to cement clinker, but its activity is low. The free CaO in steel slag is slow to hydrate due to its dense structure and coarse crystal particles. There are stability issues that limit its reuse. In recent years, many scholars and companies have carbonized steel slag to reduce its free CaO content, eliminate its stability risks, and improve its activity for reuse; phosphorus slag is a by-product of yellow phosphorus production. Because it contains a large amount of soluble phosphate and fluoride salts, it will greatly extend the setting time of cement, thereby limiting its use as an admixture. Summary of the invention

[0007] In order to solve the problems existing in the prior art, the present invention provides a tunnel grouting material and a preparation method thereof. Specifically, the present invention adopts cement as a cementitious material and adds a large amount of industrial solid waste as an admixture, wherein semi-carbonized steel slag powder is prepared by modifying steel slag, and phosphorus slag powder, carbide slag and desulfurization ash are combined as admixtures, and a water reducer and SAP particles are added as admixtures, wherein the water reducer can reduce the water consumption of the grouting material and improve the fluidity of the slurry, and the SAP particles can cooperate with the semi-carbonized steel slag powder to improve the long-term expansion performance of the grouting material, especially for the geological conditions with abundant water around the enclosure structure, to improve the anti-seepage effect of the maintenance structure.

[0008] Specifically, the tunnel grouting material of the present invention is composed of the following raw materials in parts by weight:

[0009] 100-120 parts of cement, 40-50 parts of semi-carbonized steel slag powder, 20-30 parts of phosphorus slag powder, 20-30 parts of carbide slag, 5-10 parts of desulfurized ash, 700-800 parts of fine aggregate, 7-10 parts of water reducer, 2-4 parts of SAP particles, and 80-90 parts of water.

[0010] Preferably, the semi-carbonized steel slag powder preparation process is:

[0011] ① Crush the aged converter slag particles to 3-5mm and immerse them in water for saturation.

[0012] ② Place 100 parts of saturated steel slag particles in an autoclave, add 100-120 parts of alcohol amine solution and 5-10 parts of sodium dihydrogen phosphate, and pretreat at a temperature of 120-130°C and a pressure of 0.2-0.3MPa for 2-4h.

[0013] ③ Pass carbon dioxide-containing gas into the autoclave for carbon fixation for 30-45 minutes, dry, ball-mill, and sieve to obtain the product.

[0014] Steel slag is an industrial by-product of steel smelting, and its utilization rate is low. It is usually piled up in the open air or simply landfilled as solid waste, occupying a large amount of land resources and causing soil alkalization. The volcanic ash activity of steel slag is low, the grindability is poor, and there is a large amount of free calcium oxide, which is easy to cause stability problems, limiting its application. Recently, steel slag is often carbonized to prepare carbonized steel slag powder, reducing the free calcium oxide content, thereby eliminating the hidden danger of volume stability. The present invention refers to the characteristics of free calcium oxide and the advantages of carbonization process, prepares a semi-carbonized steel slag powder and uses it for grouting materials, so that most of the stability effects are eliminated, but a certain continuous expansion ability is maintained in a humid environment. In the early hydration process of the grouting material, cement and admixtures form a large amount of calcium sulfonate as an expansion source, and the calcium carbonate particles in the semi-carbonized steel slag serve as crystal nuclei to promote the large-scale consumption of high-activity calcium oxide. The residual low-activity free calcium oxide serves as a long-term expansion source of the hardened body of the grouting material, and is gradually activated in a humid environment to achieve later continuous micro-expansion, block the seepage microchannel, and improve the anti-seepage ability of the enclosure structure.

[0015] The present invention performs preliminary rough crushing on aged converter slag and soaks it in saturated water, then adds alcohol amine and sodium dihydrogen phosphate to pretreat the saturated slag particles under high temperature and high pressure, free calcium oxide is fully wetted and contacts with a modifier, and in the subsequent carbonization process of introducing carbon dioxide, the free calcium oxide is only partially carbonized, and the generated calcium carbonate microcrystals can not only be used as a filler, but also can be used as crystal nuclei in the subsequent process to promote the hydration and expansion of the remaining free calcium oxide, and finally grinds the semi-carbonized slag powder to prepare the semi-carbonized slag powder, which is different from the carbonized slag powder in the prior art, in which the free calcium oxide content in the carbonized slag powder in the prior art has been greatly reduced, and the activity of the remaining small amount of free calcium oxide is also low, and sufficient expansion cannot be generated in the subsequent hydration process.

[0016] Preferably, the cement is at least one of Portland cement and ordinary Portland cement, and the strength grade is not less than 42.5.

[0017] Preferably, the semi-carbonized steel slag powder has a particle size of ≤45 μm and a specific surface area of ​​≥420 m 2 / kg, free calcium oxide content is 1.8-2.2%.

[0018] Preferably, in step ② of the process for preparing semi-carbonized steel slag powder, the alcoholamine is at least one of triisopropanolamine and triethanolamine, and the mass concentration of the alcoholamine solution is 25-30%.

[0019] Preferably, the CO2 concentration in the carbon dioxide-containing gas in step ③ of the semi-carbonized steel slag powder preparation process is 70-100%.

[0020] Preferably, the specific surface area of ​​the phosphorus slag powder is ≥450 m 2 / kg, the particle size of the carbide slag is ≤45μm.

[0021] The present invention further adds phosphorus slag powder, carbide slag and desulfurization ash as admixtures. Phosphorus slag powder contains soluble phosphorus, fluorine and the like which will prolong the setting time of cement. The present invention adds phosphorus slag powder and semi-carbonized steel slag powder for use together. The soluble phosphorus therein can regulate the hydration of free calcium oxide, inhibit its rapid hydration within 90 days of the hardened body of the grouting material, and make it expand controllably. The generated insoluble calcium phosphate salt is coated on the surface of the free calcium oxide, thereby further regulating its continuous expansion in a humid environment in the later period of service, and blocking the water seepage channel. , improve the anti-seepage effect of grouting materials, carbide slag and desulfurization ash can also have a certain stimulating effect on phosphorus slag powder and semi-carbonized steel slag powder, and jointly generate hydration products to interweave with cement hydration products, thereby improving the mechanical properties of grouting materials. In addition, the large amount of semi-carbonized steel slag powder, phosphorus slag powder and carbide slag causes the encapsulation of grouting materials to deteriorate, which is easy to cause slurry bleeding, especially when machine-made sand is used as fine aggregate, which makes it easier for the slurry to "slag". The addition of desulfurization ash can improve the encapsulation of the slurry for aggregates, and the workability of the slurry is greatly improved.

[0022] Preferably, the fine aggregate is at least one of machine-made sand, river sand and quartz sand, and has a fineness modulus of 2.2-2.4.

[0023] Preferably, the water reducer is a polycarboxylate water reducer with a water reduction rate of ≥25%.

[0024] Preferably, the SAP particles are acrylamide-type SAP. The SAP particles added in the present invention absorb water and expand in the initial stage of slurry mixing. After the grouting material hardens, it will gradually release water to achieve internal curing. After releasing water, the SAP particles shrink to produce closed micropores. The SAP closed pores can block the water penetration channel and improve the frost resistance of the grouting material. The presence of the SAP closed pores can also provide a certain expansion space for the remaining free calcium oxide in the semi-carbonized steel slag powder. When the enclosure structure faces water pressure, the SAP particles can further absorb part of the water and maintain it. The microcracks generated around the grouting material during service will also be compensated by the hydration of calcium hydroxide generated by the hydration of free calcium oxide and unhydrated cement and admixture particles. The moisturizing SAP particles can also provide the water required for hydration, thereby improving the compactness and impermeability of the grouting material.

[0025] The present invention also relates to a method for preparing the above tunnel grouting material, which specifically comprises the following steps:

[0026] 1) Weigh each raw material by weight,

[0027] 2) Place cement, semi-carbonized steel slag powder, phosphorus slag powder, carbide slag, desulfurization ash and SAP particles in a mixer and mix them evenly.

[0028] 3) Add fine aggregate to the mixer and mix evenly.

[0029] 4) Dissolve the water reducer in water to obtain an admixture solution.

[0030] 5) Pour the admixture solution into the mixer and mix evenly to obtain the grouting material.

[0031] In addition, it cannot be limited that the tunnel grouting material of the present invention has excellent construction effect, mechanical properties and durability, and it can also be used in grouting occasions of other projects, such as mine drilling and sealing, building foundation reinforcement, etc.

[0032] The present invention has the following technical advantages:

[0033] 1. The semi-carbonized steel slag powder prepared by the present invention meets the requirements of early stability and has the ability to continuously expand in the later stage.

[0034] 2. The present invention uses semi-carbonized steel slag powder, phosphorus slag powder, carbide slag, and desulfurized ash as admixtures to coordinately regulate the hydration process, maintain continuous expansion, ensure the expansion effect in a water-rich environment in the later stage, and jointly improve the mechanical properties and anti-seepage ability of the grouting material.

[0035] 3. The present invention adds SAP particles to achieve internal curing, and introduces SAP closed cells to improve the anti-seepage effect and frost resistance, while providing space and moisture for later expansion and crack repair.

[0036] 4. The present invention uses a large amount of admixtures that are difficult to use, saves the use of fly ash, mineral powder, and silica ash, and provides a solution for the reuse of steel slag, phosphorus slag, carbide slag, and desulfurization ash.

[0037] 5. The preparation process of the present invention is simple, the cost is low, and it has good construction performance, mechanical properties and durability. DETAILED DESCRIPTION

[0038] In order to characterize the technical effect of the present invention, grouting materials were prepared and performance tests were carried out. The cement used was P·O42.5 cement, and the specific surface area of ​​phosphorus slag powder was ≥450 m 2 / kg, carbide slag particle size ≤45μm, machine-made sand is used as fine aggregate, fineness modulus is 2.4, polycarboxylic acid water-reducing agent is used as water-reducing agent, and water reduction rate is 28%. The fluidity and compressive strength of the grouting material are tested with reference to the mortar performance test method. When testing the expansion rate, the specimen is saturated with water and wrapped with plastic wrap. The specimen is removed from the plastic wrap every 3 days, sprayed with water to moisten it, and then wrapped with plastic wrap to continue testing. "+" represents expansion and "-" represents contraction.

[0039] Example 1

[0040] The tunnel grouting material is composed of the following raw materials in parts by weight:

[0041] 120 parts of cement, 45 parts of semi-carbonized steel slag powder, 20 parts of phosphorus slag powder, 26 parts of calcium carbide slag, 6 parts of desulfurized ash, 750 parts of fine aggregate, 8 parts of water reducer, 3 parts of SAP particles, and 86 parts of water.

[0042] The semi-carbonized steel slag powder preparation process is:

[0043] ① Crush the aged converter slag particles to 3-5mm and immerse them in water for saturation.

[0044] ② Place 100 parts of saturated steel slag particles in an autoclave, add 110 parts of 25% mass concentration triisopropanolamine solution and 6 parts of sodium dihydrogen phosphate, and pretreat at a temperature of 125°C and a pressure of 0.3MPa for 3h.

[0045] ③ Pass pure carbon dioxide gas into the autoclave to fix carbon for 40 minutes, dry, ball-mill, and sieve to ≤45μm to obtain.

[0046] After testing, the grouting material has a fluidity of 220mm and good workability. The 28d compressive strength is 49.6MPa, the 3d expansion rate is -0.02%, the 7d expansion rate is 0.01%, the 28d expansion rate is 0.03%, the 90d expansion rate is 0.05%, and the 180d expansion rate is 0.06%.

[0047] Example 2

[0048] The tunnel grouting material is composed of the following raw materials in parts by weight:

[0049] 110 parts of cement, 40 parts of semi-carbonized steel slag powder, 25 parts of phosphorus slag powder, 30 parts of carbide slag, 7 parts of desulfurized ash, 750 parts of fine aggregate, 8 parts of water reducer, 3 parts of SAP particles, and 86 parts of water.

[0050] The semi-carbonized steel slag powder preparation process is:

[0051] ① Crush the aged converter slag particles to 3-5mm and immerse them in water for saturation.

[0052] ② Place 100 parts of saturated steel slag particles in an autoclave, add 110 parts of 25% mass concentration triisopropanolamine solution and 7 parts of sodium dihydrogen phosphate, and pretreat at a temperature of 120°C and a pressure of 0.3MPa for 3h.

[0053] ③ Pass pure carbon dioxide gas into the autoclave to fix carbon for 40 minutes, dry, ball-mill, and sieve to ≤45μm to obtain.

[0054] After testing, the grouting material has a fluidity of 230mm and good workability. The 28d compressive strength is 47.5MPa, the 3d expansion rate is -0.03%, the 7d expansion rate is 0.01%, the 28d expansion rate is 0.02%, the 90d expansion rate is 0.04%, and the 180d expansion rate is 0.05%.

[0055] Comparative Example 1

[0056] The grouting material is composed of the following raw materials in parts by weight:

[0057] 110 parts of cement, 40 parts of carbonized steel slag powder, 25 parts of phosphorus slag powder, 30 parts of carbide slag, 7 parts of desulfurized ash, 750 parts of fine aggregate, 8 parts of water reducer, 3 parts of SAP particles, and 86 parts of water.

[0058] The preparation process of the carbonized steel slag powder is as follows:

[0059] ① Crush the aged converter slag particles to 3-5mm and immerse them in water for saturation.

[0060] ② Place 100 parts of saturated steel slag particles in an autoclave, add 120 parts of water, and pre-treat at a temperature of 120°C and a pressure of 0.3MPa for 3 hours.

[0061] ③ Pass pure carbon dioxide gas into the autoclave to fix carbon for 90 minutes, dry, ball-mill, and sieve to ≤45μm to obtain.

[0062] After testing, the grouting material has a fluidity of 210mm and good workability. The 28d compressive strength is 47.5MPa, the 3d expansion rate is -0.04%, the 7d expansion rate is -0.06%, the 28d expansion rate is -0.07%, the 90d expansion rate is -0.08%, and the 180d expansion rate is -0.08%.

[0063] Comparative Example 2

[0064] The grouting material is composed of the following raw materials in parts by weight:

[0065] 110 parts of cement, 40 parts of semi-carbonized steel slag powder, 32 parts of fly ash, 30 parts of calcium carbide slag, 750 parts of fine aggregate, 8 parts of water reducer, 3 parts of SAP particles, and 86 parts of water.

[0066] The semi-carbonized steel slag powder preparation process is:

[0067] ① Crush the aged converter slag particles to 3-5mm and immerse them in water for saturation.

[0068] ② Place 100 parts of saturated steel slag particles in an autoclave, add 110 parts of 25% mass concentration triisopropanolamine solution and 7 parts of sodium dihydrogen phosphate, and pretreat at a temperature of 120°C and a pressure of 0.3MPa for 3h.

[0069] ③ Pass pure carbon dioxide gas into the autoclave to fix carbon for 40 minutes, dry, ball-mill, and sieve to ≤45μm to obtain.

[0070] After testing, the grouting material has a fluidity of 240mm, slurry seepage, a 28d compressive strength of 42.8MPa, a 3d expansion rate of -0.01%, a 7d expansion rate of -0.03%, a 28d expansion rate of -0.04%, a 90d expansion rate of -0.03%, and a 180d expansion rate of -0.01%.

[0071] Comparative Example 3

[0072] The grouting material is composed of the following raw materials in parts by weight:

[0073] 110 parts of cement, 43 parts of semi-carbonized steel slag powder, 25 parts of phosphorus slag powder, 37 parts of desulfurized ash, 750 parts of fine aggregate, 8 parts of water reducer, and 86 parts of water.

[0074] The semi-carbonized steel slag powder preparation process is:

[0075] ① Crush the aged converter slag particles to 3-5mm and immerse them in water for saturation.

[0076] ② Place 100 parts of saturated steel slag particles in an autoclave, add 110 parts of 25% mass concentration triisopropanolamine solution and 7 parts of sodium dihydrogen phosphate, and pretreat at a temperature of 120°C and a pressure of 0.3MPa for 3h.

[0077] ③ Pass pure carbon dioxide gas into the autoclave to fix carbon for 40 minutes, dry, ball-mill, and sieve to ≤45μm to obtain.

[0078] After testing, the fluidity of the grouting material was 220mm, compaction occurred, the 28d compressive strength was 38.1MPa, the 3d expansion rate was -0.02%, the 7d expansion rate was -0.03%, the 28d expansion rate was -0.07%, the 90d expansion rate was -0.06%, and the 180d expansion rate was -0.05%.

[0079] Comparative Example 4

[0080] The grouting material is composed of the following raw materials in parts by weight:

[0081] 110 parts of cement, 40 parts of semi-carbonized steel slag powder, 25 parts of phosphorus slag powder, 30 parts of carbide slag, 7 parts of desulfurized ash, 750 parts of fine aggregate, 8 parts of water reducer, 3 parts of SAP particles, and 86 parts of water.

[0082] The semi-carbonized steel slag powder preparation process is:

[0083] ① Crush the aged converter slag particles to 3-5mm and immerse them in water for saturation.

[0084] ② Place 100 parts of saturated steel slag particles in an autoclave, add 110 parts of 25% triisopropanolamine solution, and pretreat at 120°C and 0.3MPa for 3h.

[0085] ③ Pass pure carbon dioxide gas into the autoclave to fix carbon for 40 minutes, dry, ball-mill, and sieve to ≤45μm to obtain.

[0086] After testing, the grouting material has a fluidity of 200mm and good workability. The 28d compressive strength is 42.3MPa, the 3d expansion rate is -0.05%, the 7d expansion rate is -0.03%, the 28d expansion rate is -0.02%, the 90d expansion rate is -0.01%, and the 180d expansion rate is -0.01%.

[0087] Comparative Example 5

[0088] The grouting material is composed of the following raw materials in parts by weight:

[0089] 110 parts of cement, 40 parts of semi-carbonized steel slag powder, 25 parts of phosphorus slag powder, 30 parts of carbide slag, 7 parts of desulfurized ash, 750 parts of fine aggregate, 8 parts of water reducer, 3 parts of SAP particles, and 86 parts of water.

[0090] The semi-carbonized steel slag powder preparation process is:

[0091] ① Crush the aged converter slag particles to 3-5mm and immerse them in water for saturation.

[0092] ② Place 100 parts of saturated steel slag particles in an autoclave, add 110 parts of 25% triisopropanolamine solution and 7 parts of sodium dihydrogen phosphate, and pretreat at 30°C and 0.1MPa for 3h.

[0093] ③ Pass pure carbon dioxide gas into the autoclave to fix carbon for 40 minutes, dry, ball-mill, and sieve to ≤45μm to obtain.

[0094] After testing, the grouting material has a fluidity of 210mm and good workability. The 28d compressive strength is 44.1MPa, the 3d expansion rate is -0.07%, the 7d expansion rate is -0.09%, the 28d expansion rate is 0.03%, the 90d expansion rate is 0.01%, and the 180d expansion rate is -0.03%.

[0095] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A tunnel grouting material, characterized in that: It is composed of the following raw materials in parts by weight: 100-120 parts of cement, 40-50 parts of semi-carbonized steel slag powder, 20-30 parts of phosphorus slag powder, 20-30 parts of calcium carbide slag, 5-10 parts of desulfurized ash, 700-800 parts of fine aggregate, 7-10 parts of water reducer, 2-4 parts of SAP particles, 80-90 parts of water, The semi-carbonized steel slag powder preparation process is: ① Crush the aged converter slag particles to 3-5mm and immerse them in water for saturation. ② Place 100 parts of saturated steel slag particles in an autoclave, add 100-120 parts of alcohol amine solution and 5-10 parts of sodium dihydrogen phosphate, and pretreat at a temperature of 120-130°C and a pressure of 0.2-0.3MPa for 2-4h. ③ Pass carbon dioxide-containing gas into the autoclave for carbon fixation for 30-45 minutes, dry, ball-mill, and sieve to obtain the product.

2. The tunnel grouting material according to claim 1, characterized in that: The cement is at least one of silicate cement and ordinary silicate cement, and the strength grade is not less than 42.

5.

3. The tunnel grouting material according to claim 1, characterized in that: The particle size of the semi-carbonized steel slag powder is ≤45μm, and the specific surface area is ≥420m 2 / kg, free calcium oxide content is 1.8-2.2%.

4. The tunnel grouting material according to claim 1, characterized in that: In step ② of the semi-carbonized steel slag powder preparation process, the alcohol amine is at least one of triisopropanolamine and triethanolamine, and the mass concentration of the alcohol amine solution is 25-30%.

5. The tunnel grouting material according to claim 1, characterized in that: The CO2 concentration in the carbon dioxide-containing gas in step ③ of the semi-carbonized steel slag powder preparation process is 70-100%.

6. The tunnel grouting material according to claim 1, characterized in that: The specific surface area of ​​the phosphorus slag powder is ≥450 m 2 / kg, the particle size of the carbide slag is ≤45μm.

7. The tunnel grouting material according to claim 1, characterized in that: The fine aggregate is at least one of machine-made sand, river sand and quartz sand, and has a fineness modulus of 2.2-2.

4.

8. The tunnel grouting material according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate is ≥25%.

9. The tunnel grouting material according to claim 1, characterized in that: The SAP particles are acrylamide-type SAP.

10. The method for preparing the tunnel grouting material according to any one of claims 1 to 9, characterized in that: The steps include: 1) Weigh each raw material by weight, 2) Place cement, semi-carbonized steel slag powder, phosphorus slag powder, carbide slag, desulfurization ash and SAP particles in a mixer and mix them evenly. 3) Add fine aggregate to the mixer and mix evenly. 4) Dissolve the water reducer in water to obtain an admixture solution. 5) Pour the admixture solution into the mixer and mix evenly to obtain the grouting material.

Citation Information

Patent Citations

  • Drifting sand layer and gravel stratum water-moving double-liquid high pressure slip-casting water-blocking construction method

    CN101255698A

  • High performance slip casting material for sealing freezing holes in mines and preparation method thereof

    CN102351480A

  • Mineral flexible hole-sealing and grouting material

    CN109437771A

  • Hydrated and carbonized composite hardened cementing material based on steel slag and preparation method of hydrated and carbonized composite hardened cementing material

    CN114538806A

  • Method for decarburizing industrial flue gas and cooperatively preparing steel slag concrete and obtained product

    CN114950119A

Cited By

  • Composite grouting material and preparation method thereof

    CN122233749A